(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This scientific investigation attempt’s by differently-abled employees began as a quest into their own psychological empowerment. The authors attempted to study the relationship between psychological empowerment of differently-abled ( visually impaired) employees and their work engagement across different sectors in India during CIVID19 lockdown. The research design employed both quantitative and qualitative data through surveys and interviews. Results indicate a significant relationship between psychological empowerment and work engagement. The study has implications for human resource professionals, managers and researchers.